Looking Back: Reviewing the Challenges of Policy Development During the COVID-19 Pandemic for a TNE Partnership in Higher Education - Bremner, Duncan James; Ansari, Imran Shafique; MacDougall, Jennifer; Hussain, Sajjad; Ma, Mingda; Ponciano, Joao; Liu, Xingang; Gamage, Kelum A. A.; Abbas, Hasan; Imran, Muhammad Ali (Frontiers in Education, 2021)
This paper takes a retrospective view of the year 2020, with a focus on how Higher Education policy development was undertaken on a Transnational Education (TNE) program between the University of Glasgow (UofG) and the University of Electronics, Science and Technology in Chengdu (UESTC), China in response to the COVID-19 pandemic. It explores the approach to policy development under normal circumstances, contrasting this with the approach taken during the emergence of the epidemic and how the unfolding situation impacted on those policies. It demonstrates how the application of management tools for scenario planning and crisis management can be used effectively to develop a clear and prescriptive policy for staff. It also demonstrates how the use of such tools, combined with careful analysis and planning, can minimize disruption to student learning, teaching, and assessment. The paper then goes on to explain the creation and implementation of policies addressing three main areas: learning and teaching, Final Year Projects, and assessment. Finally, it reflects on the student and staff perspectives on the policies, considering how this information might be used to enhance the policy development process in future.